Technological Advancement In The Society 5.0 Era For Notary In Indonesia: Glory Or Obsolete? - Agustini; Nurlaily; Triana Dewi Seroja (LEGAL BRIEF, 2022)
The development of the legal profession is changing at an extraordinary speed, such as in the field of technology. The legal needs in society will be met by new entities, including technology companies that provide document creation systems and artificial intelligence systems to support legal services. But in the era of society 5.0, with digital advances and the emergence of artificial intelligence machines and big data, this eventually led to a change in the perspective and way of individuals in terms of law, which turned into an "alarm" for disruption to the legal profession, especially advocate offices. notaries, including courts, which at first were often ignored because of the emergence of artificial intelligence. This study aims to answer how the legal profession, especially the notary position, is associated with technological developments in the era of society 5.0. The research method used is normative juridical, in which the researcher examines this research by applying secondary data. The study of secondary data means the collection/study of data through literature studies, in the form of written regulations, books and journals. The author explores previous studies that discuss artificial intelligence in notary positions. The author also sees the latest developments in "competition" between the human legal profession, especially in the notary position and artificial intelligence. More sophisticated technology will replace something technological in nature, so the legal profession whose legal method is mechanical will be replaced by artificial intelligence that is faster and more accurate